Network pharmacology and molecular docking study to reveal the potential anticancer activity of Oscillatoxin D, E, and F marine cytotoxins - D. Luthfiana; M. Soleha; A. Prasetiyo; W. A. Kusuma; R. Fatriani; L. Nurfadhila; N. Yunitasari; A. H. Ahkam; T. L. Wargasetia; R. Irfandi; A. N. M. Ansori; V. D. Kharisma; et al. (Пищевые системы)
Oscillatoxins (OTXs) are cytotoxins produced by some marine cyanobacteria. Their unique structures show a great potency as an anticancer agent. The limited availability of OTX derivatives in nature provides little information about their biological activity. Some of OTX activities have been tested in the in vitro or in vivo studies toward cancer cell lines, but their exact mechanism of action on the target is unclear. In this study, we used the network pharmacology analysis method to predict the target and mechanism of action of oscillatoxin D (OTX-D), 30 methyl oscillatoxin D (30-methyl-OTX-D), oscillatoxin E (OTX-E), and oscillatoxin F (OTX-F). There are 20 possible targets of the four compounds toward cancer, and the main targets of them are PIK3CA, CDK1, and MTOR. This was also followed by the molecular docking study to understand the interaction between the four compounds and their targets. Molecular docking showed that the four compounds interacted well with the key targets. In this study, four derivatives of OTXs and their three key targets for the anticancer action were revealed suggesting multiple signaling pathways, including PD-L1 expression and PD‑1 checkpoint pathway in cancer, proteoglycans in cancer, and pathways in cancer, establishing a theoretical framework for the further experimental study.